Prevenção de câncer cérvico-uterino. Perfil das mulheres com câncer Invasor - Ferrigno, Robson (2023)
From November 1989 through November 1990, 120 cases of invasive cervical cancer were referred to the Department of Radiation Oncology at Dr. Mário Gatti Hospital/Pontifical Catholic University of Campinas. Because most of the patients was diagnosed in advanced stages, a survey was done to assess the circumstances that leaded them to invasive cervical cancer. One hundred and five women were asked about their characteristics and relations to Pap smears. Fifty-seven patients (54.3%) had never done the exam, 35 (33.3%,) had done it in an irregular way or more than three years previousiy and 13 (12.4%) had done it regularly. Eighty-six women (82%,) had knowledge about the exam and 76 (72%) were knowing where it can be done. Among 86 women who had knowledge about the exam, 38 (44%,) had never done it. The survey data indicate that most of the patients was informed about the exam but not awared about the importance of it. The low level of education in health seemed to be the main problem involved in cervical cancer screening in the studied population.